P236 Relationship Between Bone Mineral Density And Bone Turnover Markers In Severe Asthma Patients On Systemic Corticosteroids. (10th November 2014) - Brice, HGT; Farrant, JP; Fowler, SJ; Holmes, LJ; Tang, J; Washbourne, C; Piec, I; Fraser, W; Sweeney, J; Heaney, LG; Niven, RM
Abstract : Objectives: Measure bone turnover markers (BTM) CTx, P1NP and bone-specific alkaline phosphatase (BsALP) in a severe asthma population using systemic corticosteroids (SCS). Assess bone mineral density (BMD) change in regional severe asthma clinics. Background: Severe asthma often requires regular SCS use. SCS cause several adverse effects including reduced bone metabolism; resorption is increased and formation is decreased resulting in osteoporosis. DXA scans monitor BMD in the hip and spine every 3–5 years. BMD decrease is treated with bone sparing medication (BSM), but treatment is retrospective and response takes years to assess. BTM represent markers of systemic bone metabolism and may offer a more efficient alternative. CTx is a resorption marker, P1NP and BsALP are formation markers. Method: Patients attending Manchester or Belfast severe asthma clinic with two or more DXA scans were identified from case files. We measured BTM in Manchester severe asthma patients and a control group of Manchester severe asthma patients requiring less than 3 courses of steroids per year. Using case files we collected data including DXA scan results, SCS use and osteoporosis risk factors. Results: BMD change and BTM did not correlate overall (patients n = 78, controls n = 18) but correlated negatively in patients where the most recent DXA was Conclusion: This study has confirmed that BTM may be potentially used as a surrogate for BMD measurement; however a more a prospective study where BTM are measured at the time of two DXA scans which are years apart is required.